Communication in nursing: A learning exercise for teachers and students - M. Hammond (AOSIS, 1984)
In the Department of Community Health, University of the Witwatersrand, self-directed learning materials have been used for fourthyear medical students since January 1983. Student feedback has been very positive and we have seen significant increases in marks when compared with conventional didactic handouts. It is believed that this teaching method has great potential for many other groups of adult learners - nurses among them.